Absent Appendix - Maitra, Tapash Kumar; Roy, Sharmistha; Mondal, Samiron Kumar; Mahjabin, Sahla (Bangladesh Critical Care Journal, 2013)
Congenital absence of the vermiform appendix is a rare condition in human that many well-experienced surgeons have never seen. The fact that congenital absence of the vermiform appendix has been reported on several occasions confirms its existence and should be kept in mind. A thorough and meticulous search of the entire ileocecal region and mobilization of the cecum and ascending colon should be carried out before the diagnosis is made. But, it should also be kept in mind that early cessation of appendiceal anlage can result in very tiny ones. DOI: http://dx.doi.org/10.3329/bccj.v1i2.17207 Bangladesh Crit Care J September 2013; 1 (2): 109-110